Aesthetic transformation of the smile with strategic additions in composite resin: Clinical case (Research, Society and Development, 2021)
Diastemas are interdental spaces larger than 0.5mm with a multifactorial etiology that can compromise the aesthetics of the smile. Various forms of treatment have been reported in the literature for their correction, such as: orthodontics, surgery, use of ceramic laminates or composite resins. However, the therapeutic choice depends on the identification of its etiology. The aim of this study is to report a clinical case of closing diastemas with direct composite resin, using a silicone palatal guide, after orthodontic treatment. Initially, it was carried out: color selection of the composite resin with the hydrated dental surface; absolute isolation of the operative field; prophylaxis with pumice paste and water; conditioning with 37% phosphoric acid (30 seconds in enamel); removal with water / air spray for twice the conditioning time; drying; application of universal adhesive (two layers); light curing (20 seconds); making the palatal shell, shaping the contours and surfaces in composite resin; removal of isolation from the operative field; occlusal adjustment and polishing. It is concluded that: 1) The use of composite resins for the closure of diastemas and dental remodeling with incisal enlargement represents. an affordable choice and can be an alternative for orthodontic finishes, in closing diastemas. 2) The use of the silicone guide makes it easier to define height; contours and construction of the palatal wall, minimizing the need for adjustments. 3) The therapy employed is effective for the aesthetic improvement of the smile, being a conservative, reversible, predictable technique that has led to patient satisfaction.